2021
DOI: 10.5380/ce.v26i0.72327
|View full text |Cite
|
Sign up to set email alerts
|

Declínio Das Taxas De Internação Hospitalar Por Doenças Cardiovasculares Em Adultos No Brasil

Abstract: Objetivo: analisar a tendência das taxas de internação hospitalar por doenças cardiovasculares em adultos no Brasil.Método: estudo ecológico, de séries temporais, das taxas de internação por doenças cardiovasculares em adultos por sexo, faixa etária e região de residência no Brasil no período de 2005 a 2016. Foram utilizados os dados do Sistema de Informações Hospitalares do Sistema Único de Saúde. Para as análises de tendência, utilizaram-se modelos de regressão polinomial.Resultados: detectou-se tendência de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Over the twelve years surveyed, Paraná, Santa Catarina, Rio Grande do Sul and Minas Gerais were the states with the highest rates of hospitalization for CVDs, a fact that can be justified by the Southeast and South regions having the highest rates of individuals with hypertension in the country (23.3% and 22.9% respectively), while the lowest index (14.5%) (10) is concentrated in the North region. SAH is considered to be the most important cardiovascular risk factor, as it is associated with the development of chronic kidney disease, stroke, Acute Myocardial Infarction(AMI) and coronary artery diseases, in addition to a direct association with cardiovascular and renal morbidity and mortality (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the twelve years surveyed, Paraná, Santa Catarina, Rio Grande do Sul and Minas Gerais were the states with the highest rates of hospitalization for CVDs, a fact that can be justified by the Southeast and South regions having the highest rates of individuals with hypertension in the country (23.3% and 22.9% respectively), while the lowest index (14.5%) (10) is concentrated in the North region. SAH is considered to be the most important cardiovascular risk factor, as it is associated with the development of chronic kidney disease, stroke, Acute Myocardial Infarction(AMI) and coronary artery diseases, in addition to a direct association with cardiovascular and renal morbidity and mortality (11) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a spatial study conducted in South Korea also found a strong spatial correlation with hypertension, linked to socio-demographic and economic indicators (13) . Thus, it is suggested that the population of the Southeast and South regions have better access to diagnostic tests and also to medications since, in these regions, the largest number of people is concentrated who report having had tests such as total cholesterol, triglycerides, serum analysis of glucose, and that refer to the use of antihypertensive medications (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Como limitações deste estudo, pode-se apontar que o SIH/SUS apresenta subnotificações em algumas localidades. Em Figueiredo et al (2021), os autores não incluem informações sobre comorbidades e variáveis sociais que poderiam ser úteis para análises de utilização de serviços de saúde. Em Costa et al (2010), múltiplas internações por condições evitáveis de um mesmo paciente não puderam ser identificadas e deve ser observado que o SIH/SUS contempla apenas as internações financiadas pelo SUS (Figueiredo et al, 2021;Tagliaria, Murarob & Ferreira, 2016).…”
Section: Considerações Finaisunclassified
“…As doenças cardiovasculares (DCV) englobam um grupo de afecções que afetam o coração, os vasos sanguíneos e o suprimento vascular de tecidos e órgãos. Esse grupo de doenças ocupa o primeiro lugar entre as causas de mortalidade não transmissíveis no mundo, fato este que ocorre devido a ineficácia do rastreio e controle dos fatores de risco associados ao desenvolvimento e agravamento dessas doenças (FIGUEIREDO et al, 2020).…”
unclassified